Civil society and medical product access in Africa: Lessons from COVID-19 - Wale, Janet L.; Sehmi, Kawaldip; Kamoga, Regina; Ssekubugu, Robert (Frontiers in Medical Technology, 2023)
Understanding health as a human right creates a legal obligation on countries to ensure access to timely, acceptable, and affordable health care. We highlight the importance of a meaningful role for civil society in improving access to well-regulated quality medical products in Africa; to support and be part of a regional social contract approach following the access issues that have been particularly evident during the COVID-19 pandemic. We argue that African communities have a clear participatory role as important stakeholders in the regulatory lifecycle. Solidarity is important for a cohesive approach as formal government healthcare infrastructure may be minimal for some countries, with little training of communities available for disease management and insufficient money to fund people to organise and deliver health care. Some of the issues for civil society engagement with multi-stakeholders, and possible mitigating strategies, are tabulated to initiate discussion on facilitators and concerns of governments and other stakeholders for meaningful participation by patients, communities and civil society within a regional regulatory lifecycle approach. Solidarity is called for to address issues of equity, ethics and morality, stigmatisation and mutual empowerment – to sustainably support the region and national governments to develop greater self-sufficiency throughout the regulatory lifecycle. By creating a participatory space, patients, communities and civil society can be invited in with clear missions and supported by well-defined guidance to create a true sense of solidarity and social cohesion. Strong leadership coupled with the political will to share responsibilities in all aspects of this work is key.